Some Features of Language Use in Yoruba Traditional Medicine - Adegbite, Wale (2014)
Yoruba traditional medicine (YTM) is a system which basically incorporates a four-square intersection of two pairs of terms in relation to medicine, viz. positive/negative and personal/communal. In the intersection of 'positive personal' medicine which is catered for by the data for this study, the goal is for a herbalist, or a priest of some divinity, to diagnose and treat an illness of a client or patient where the patient is a child, friend or relation of the client. Herbalists deal in various kinds of medicine though many of them may treat cases of different types, they normally have different areas of specialty e.g. gynaecology, paediatrics, traditional midwifery, orthopaedics, psychiatry etc. However, the diviners or priests are well reputed for handling complex cases that are linked to supernatural causation.